2010
DOI: 10.1253/circj.cj-10-0210
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Sirolimus-Eluting Stent Implantation to Treat Sirolimus-Eluting Stent and Bare-Metal Stent Restenosis

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp lthough drug-eluting stents (DES) have significantly decreased the incidence of in-stent restenosis (ISR) and the need for repeated revascularization compared with bare-metal stents (BMS), 1-5 DES restenosis still develops and ISR remains an important clinical issue especially for patients with highly complex lesions. 2-7 The increasing use of DES in complex settings coupled with the worldwide implantation of >10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A). Twenty‐five single arm and 13 comparative studies with a total of 7,474 patients with DES ISR were included in this analysis . Of the 13 comparative studies (including 3,642 patients with DES ISR), 11 studies compared outcomes between repeat DES and BA, 3 studies compared DEB and BA, and only one study compared DEB with DES (ISAR DESIRE 3) for the management of DES ISR.…”
Section: Resultsmentioning
confidence: 99%
“…A). Twenty‐five single arm and 13 comparative studies with a total of 7,474 patients with DES ISR were included in this analysis . Of the 13 comparative studies (including 3,642 patients with DES ISR), 11 studies compared outcomes between repeat DES and BA, 3 studies compared DEB and BA, and only one study compared DEB with DES (ISAR DESIRE 3) for the management of DES ISR.…”
Section: Resultsmentioning
confidence: 99%
“…After the introduction of DES with remarkable efficacy for restenosis, DES has become the treatment of choice for BMS restenosis patients. 25, 26 In most of the present study period, however, DES was not available in Japan. Therefore, POBA, especially cutting balloon, was widely used for BMS restenosis, which resulted in a relatively higher TLR rate.…”
Section: Discussionmentioning
confidence: 96%
“…In the past, the studies comparing DES to ICBT for the treatment of ISR have paid more attention to BMS restenosis, but less to DES restenosis. A recent published paper showed that the incidences of late restenosis, ischemia‐driven TLR, and MACE are higher after repeated SES implantation in ISR lesions treated with SES than in those treated with BMS 30. Therefore, ICBT remains a proven method of restenosis prevention for the treatment of ISR, and its role in treating DES restenosis remains to be studied.…”
Section: Discussionmentioning
confidence: 99%